2013
DOI: 10.1002/esp.3416
|View full text |Cite
|
Sign up to set email alerts
|

The formation of supraglacial debris covers by primary dispersal from transverse englacial debris bands

Abstract: International audience: Glaciological controls on debris cover formation are investigated from the perspective of primary dispersal of supraglacial debris across a melting ice surface. This involves the migration of angled debris septa outcrops across a melting, thinning glacier ablation zone. Three measures of a glacier ' s ability to evacuate supraglacial debris are outlined: (1) a concentration factor describing the focusing of englacial debris into specific supraglacial mass loads; (2) the rate of migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
141
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(148 citation statements)
references
References 70 publications
4
141
1
2
Order By: Relevance
“…At the system scale, atypical characteristics differentiate the study sites from the larger and bare-ice glacier stereotype: the small size of the upslope firn and bare-ice zones and the associated large relative area of debris-covered glacier zones, the existence of marginal rock glaciers and the overall very high amount of debris in comparison with the glacier size. The glacier zones are extensively covered by a coarse-grained debris layer that thickens downglacier due to flux emergence, compressive stress and ice melt (Kirkbride and Deline, 2013). This also explains the debris concentration increase in the glacier margins.…”
Section: Internal Structurementioning
confidence: 98%
See 2 more Smart Citations
“…At the system scale, atypical characteristics differentiate the study sites from the larger and bare-ice glacier stereotype: the small size of the upslope firn and bare-ice zones and the associated large relative area of debris-covered glacier zones, the existence of marginal rock glaciers and the overall very high amount of debris in comparison with the glacier size. The glacier zones are extensively covered by a coarse-grained debris layer that thickens downglacier due to flux emergence, compressive stress and ice melt (Kirkbride and Deline, 2013). This also explains the debris concentration increase in the glacier margins.…”
Section: Internal Structurementioning
confidence: 98%
“…Two main causes, enhanced by the acceleration of ice melt since the mid-1980s (e.g., Zemp et al, 2015), explain the current extent and thickening of supraglacial debris cover observed in mountainous regions (Kirkbride and Deline, 2013). Firstly, the deglaciation of rockwalls and permafrost degradation increase the debris supply to glacier systems (Bosson et al, 2015;Deline et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result complete summer balances from debris-covered glaciers are sparse (WGMS, 2008). Measurements of englacial debris concentrations and distribution are yet more difficult to obtain (e.g., Kirkbride and Deline, 2013). In addition, exploration of century-scale response of debris-covered glaciers is limited by short satellite and observational periods (Bolch et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the role played by debris on the surface mass balance of glaciers and, in turn, on the glacier response to climate change remains unclear (Kääb et al, 2012). Indeed, this debris layer insulates the glacier surface from the atmosphere when it reaches a sufficient thickness and complicates the response to climate change compared to clean-ice glaciers (Jouvet et al, 2011;Kirkbride and Deline, 2013;Østrem, 1959;Pellicciotti et al, 2015).…”
Section: Introductionmentioning
confidence: 99%